Increased expression of CXCR3 axis components and matrix metalloproteinase in pediatric inflammatory bowel disease patients. Issue 6 (10th November 2014) - Jimbo, Keisuke; Ohtsuka, Yoshikazu; Kojima, Yuko; Hosoi, Kenji; Ohbayashi, Naho; Ikuse, Tamaki; Aoyagi, Yo; Fujii, Tohru; Kudo, Takahiro; Shimizu, Toshiaki
Abstract: Background: Although pediatric inflammatory bowel disease (IBD) is characterized by extensive intestinal involvement and rapid early progression, the precise cause and specific factors involved in disease aggravation have not been well established. The aim of this study was to investigate the pathogenesis of pediatric IBD. Methods: The expression of inflammatory molecules in colon samples taken from active ulcerative colitis (UC) and Crohn's disease (CD) patients was compared with those of controls. Three children each with UC and CD in both the active and remission phase and their controls were enrolled, and the inflammatory gene expression in the mucosa was examined by microarray. Additionally, six children from each group were further enrolled in a real‐time reverse transcription polymerase chain reaction and an immunohistochemical study to examine the expression of CXCL9, 10, 11, CXCR3, matrix metalloproteinase (MMP)‐1, ‐3, ‐7, and ‐10. Results: The microarray analysis revealed enhanced expression of the CXCL9, 10, and 11 genes in the active phase of CD. The expression of MMP‐1, ‐3, ‐7, and ‐10 was significantly enhanced in the active phase of UC. These changes were also confirmed by real‐time reverse transcription polymerase chain reaction. Immunohistochemical analysis revealed enhanced expression of CXCL9, 10, and 11 in both the lamina propria and epithelial cells in these patients. CXCR3‐positive cells were also confirmed in the lamina propria. The expression of MMP‐1, ‐3, ‐7, and ‐10 was also enhanced in the mucosal epithelial cells and the lamina propria in both CD and UC patients. Conclusions: These findings suggest that CXCR3 axis components and MMP play an important role in the mucosal damage in pediatric IBD.